Come Rain, Come Shine: Peatland Carbon Dynamics Shift Under Extreme Precipitation - Barel, Janna M.; Moulia, Vincent; Hamard, Samuel; Sytiuk, Anna; Jassey, Vincent E. J. (Frontiers in Environmental Science, 2021)
Precipitation patterns are becoming increasingly extreme, particularly at northern latitudes. Current climate models predict that this trend will continue in the future. While droughts have been repeatedly studied in many ecosystems over the last decades, the consequences of increasingly intense, but less frequent rainfall events, on carbon (C) cycling are not well understood. At northern latitudes, peatlands store one third of the terrestrial carbon and their functioning is highly dependent on water. Shifts in rainfall regimes could disrupt peatland C dynamics and speed-up the rates of C loss. How will these immense stocks of C be able to withstand and recover from extreme rainfall? We tested the resistance and resilience effects of extreme precipitation regimes on peatland carbon dioxide (CO2) and methane (CH4) fluxes, pore water dissolved organic carbon (DOC) and litter decomposition rates by exposing intact peat cores to extreme, spring-time rainfall patterns in a controlled mesocosm experiment. We find that more intense but less frequent rainfall destabilised water table dynamics, with cascading effects on peatland C fluxes. Decomposition and respiration rates increased with a deeper mean water table depth (WTD) and larger WTD fluctuations. We observed similar patterns for CO2 uptake, which were likely mediated by improved vascular plant performance. After a three-week recovery period, CO2 fluxes still displayed responses to the earlier WTD dynamics, suggesting lagged effects of precipitation regime shifts. Furthermore, we found that CH4 emissions decreased with deeper mean WTD, but this showed a high resilience once WTD dynamics stabilised. Not only do our results illustrate that shifting rainfall patterns translate in altered WTD dynamics and, consequentially, influence C fluxes, they also demonstrate that exposure to altered rainfall early in the growing season can have lasting effects on CO2 exchange. Even though the increased CO2 assimilation under extreme precipitation patterns signals peatland resistance under changing climatic conditions, it may instead mark the onset of vascular plant encroachment and the associated C loss.